2020
DOI: 10.3390/ijerph17072313
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age, Gender, and Job on Skin Conductance Response among Smartphone Users Who are Prohibited from Using Their Smartphone

Abstract: The smartphone is a widely used and rapidly growing phenomenon worldwide, and problematic smartphone use is common in our society. This study’s objective was to examine the gender difference of baseline and post-intervention skin conductance response (SCR) among smartphone users and explore the relationships among problematic smartphone use level, anxiety level, and SCR changes by evaluating SCR, the Zung Self-Rating Anxiety Scale score, and the Chinese version of the Smartphone Addiction Inventory (SPAI) scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
5
0
1
Order By: Relevance
“…Similarly, the idea of digital nativity (Prensky, 2001;Wang, Sigerson, & Cheng, 2019) suggests that young adults who have grown up in a world where there has always been the internet, social media, and smartphones are more likely to 'naturally' use smartphone technology compared to older generations (digital immigrants). Other researchers have taken a developmental perspective by highlighting how certain age groups may be more susceptible to developing problematic smartphone use based on their life stage (Busch & McCarthy, 2020;Csibi, Griffiths, Demetrovics, & Szabo, 2019;Hsieh et al, 2020). For example, between the ages of 18 to 30, people may be more likely to be socializing and engaging in romantic relationship formation that can be facilitated via smartphone applications (e.g.…”
Section: Age and Smartphone Usementioning
confidence: 99%
“…Similarly, the idea of digital nativity (Prensky, 2001;Wang, Sigerson, & Cheng, 2019) suggests that young adults who have grown up in a world where there has always been the internet, social media, and smartphones are more likely to 'naturally' use smartphone technology compared to older generations (digital immigrants). Other researchers have taken a developmental perspective by highlighting how certain age groups may be more susceptible to developing problematic smartphone use based on their life stage (Busch & McCarthy, 2020;Csibi, Griffiths, Demetrovics, & Szabo, 2019;Hsieh et al, 2020). For example, between the ages of 18 to 30, people may be more likely to be socializing and engaging in romantic relationship formation that can be facilitated via smartphone applications (e.g.…”
Section: Age and Smartphone Usementioning
confidence: 99%
“…We need to consider leveraging personalized models, DA, and unlabeled data simultaneously. As a part of our future work, we will divide participants into different clusters based on their demographic information since the previous research has shown that the physiological data are associated with participants' demographic information [46], [47]. By studying the stress status of different groups, we might achieve more accurate stress detection results according to other groups of people.…”
Section: User Adaptationmentioning
confidence: 99%
“…Similarly, the idea of digital nativity (Prensky, 2001;Wang, Sigerson, & Cheng, 2019) suggests that young adults who have grown up in a world where there has always been the internet, social media, and smartphones are more likely to 'naturally' use smartphone technology compared to older generations (digital immigrants). Other researchers have taken a developmental perspective by highlighting how certain age groups may be more susceptible to developing problematic smartphone use based on their life stage (Busch & McCarthy, 2020;Csibi, Griffiths, Demetrovics, & Szabo, 2019;Hsieh et al, 2020). For example, between the ages of 18 to 30, people may be more likely to be socializing and engaging in romantic relationship formation that can be facilitated via smartphone applications (e.g.…”
Section: Age and Smartphone Usementioning
confidence: 99%